2011
DOI: 10.1186/1475-2875-10-44
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of clinical efficacy and in vitro sensitivity of Plasmodium vivax to chloroquine in area along Thai Myanmar border during 2009-2010

Abstract: Background: In Thailand, the proportion of Plasmodium vivax infection has become equal to Plasmodium falciparum. Reports of a trend of gradual decline of in vitro sensitivity of P. vivax to chloroquine in some areas of the country, together with accumulating evidences of chloroquine resistance P. vivax in other parts of the world, emphasize the need for closely and continuously monitoring clinical efficacy in conjunction with in vitro sensitivity of P. vivax isolates. Methods: The study was conducted at Mae Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
(56 reference statements)
2
23
0
Order By: Relevance
“…Clinical observations in Thailand in the past showed either complete sensitivity (29)(30)(31)(32) or only small proportions of patients developing recurrent parasitemia within 28 days (33,34). Similarly, in the neighboring region of China's Yunnan Province, longitudinal monitoring suggested that CQ efficacy remained relatively unchanged, with 1.5% (9/603) patients experiencing late clinical failure (35).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations in Thailand in the past showed either complete sensitivity (29)(30)(31)(32) or only small proportions of patients developing recurrent parasitemia within 28 days (33,34). Similarly, in the neighboring region of China's Yunnan Province, longitudinal monitoring suggested that CQ efficacy remained relatively unchanged, with 1.5% (9/603) patients experiencing late clinical failure (35).…”
Section: Discussionmentioning
confidence: 99%
“…This improvement in systemic exposure of CQ/DECQ should benefit treatment of patients, particularly in the light of accumulating reports on increasing level of CQ resistant P. vivax. Results of high clinical efficacy of CQ (100%) from various studies in Thailand in larger numbers of patients support this supposition (Muhamad et al, 2011). Since all patients responded well to treatment with no reappearance of parasitemia during the follow up period, relationship between MIC of CQ/DECQ and clinical efficacy could not be assessed in this study.…”
Section: General Pharmacokinetic Propertiesmentioning
confidence: 63%
“…The study was conducted 15 years after the first study in a larger number of patients admitted to Mae Tao clinic for migrant workers in Tak province of Thailand, the area with multidrug resistant P. falciparum along the ThaiMyanmar border. This population-based pharmacokinetic study was also part of the clinical study carried out during 2010-2011 to monitor the clinical efficacy and in vitro sensitivity of P. vivax isolates to CQ in 75 patients with P. vivax malaria (Muhamad et al, 2011). A two-compartment model was best fit with the concentration-time profiles of both CQ and DECQ, with a one transit compartment model for the absorption of CQ.…”
Section: General Pharmacokinetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations